Trends, challenges, and opportunities for massive open online courses (MOOCs) as the future of education in learning science - Ega Kornia; Happy Komikesari; Antomi Saregar (Journal of Advanced Sciences and Mathematics Education, 2022)
The purpose of this research is to identify trends, challenges, and opportunities for Massive Open Online Courses (MOOCs) as future science education. The method used in this research is a descriptive method with a bibliometric approach. Secondary data was used in this study in the form of scientific articles sourced from the Scopus database in the 2016-2021 period. Data collection uses Publish or Perish (PoP) software. The number of articles obtained was 200. All articles have been selected according to the criteria determined by the researcher. Mendeley software was used to manage metadata so that the final number of articles was 92. MOOCs, as a future educational trend, are becoming a flexible learning system that many people can follow to develop skills and knowledge. The challenge of MOOCs as future education is in the field of time and process. Then, from the results of the bibliometric analysis obtained, the growth of research related to MOOCs in the field of cooperative/collaborative learning is still relatively small, so further research related to cooperative/collaborative learning needs to be carried out.